The Perfect Facade (A Jessie Hunt Psychological Suspense Thriller-Book Twelve) - Blake, Pierce (Lukeman Literary, 2021)
"A masterpiece of thriller and mystery. Blake Pierce did a magnificent job developing characters with a psychological side so well described that we feel inside their minds, follow their fears and cheer for their success. Full of twists, this book will keep you awake until the turn of the last page." --Books and Movie Reviews, Roberto Mattos (re Once Gone) THE PERFECT FACADE is book #12 in a new psychological suspense series by bestselling author Blake Pierce, which begins with The Perfect Wife, a #1 bestseller (and free download) with over 500 five-star reviews. A group of suburban moms go out to a high-end hotel in the big city to celebrate their 40th birthday, and the night gets wild-too wild. When they wake from their sordid night to find a dead body amongst them, Jessie must unravel what happened that night. Could the murderer be one of them? Or are they being targeted? A fast-paced psychological suspense thriller with unforgettable characters and heart-pounding suspense, THE JESSIE HUNT series is a riveting new series that will leave you turning pages late into the night. Books #13 (THE PERFECT IMPRESSION), #14 (THE PERFECT DECEIT) and #15 (THE PERFECT MISTRESS) are now also available.
Keywords: Dobrodružství, napětí, thrillery; Krimi, detektivky